Ecological risk assessment of some heavy metals in sediments in the Dong Nai River section flowing through Binh Duong Province, Vietnam - Huynh, An The; Ho, Lien Bich; Nguyen, Tuyet Anh Huynh (Journal of Degraded and Mining Lands Management, 2025)
This study assessed heavy metal contamination and ecological risk in the sediments of the Dong Nai River section flowing through Binh Duong Province, Vietnam. Four monitoring stations (DN1, DN2, DN3, DN4) were established to analyze the concentrations of heavy metals, including arsenic (As), copper (Cu), zinc (Zn), lead (Pb), cadmium (Cd), and chromium (Cr). The results indicated that the concentrations of heavy metals were generally low and within acceptable limits established by Vietnam national standards (QCVN 43:2012/BTNMT). Notably, chromium and arsenic exhibited the highest concentrations among the metals analyzed. The Degree of Contamination (Cd) across the sampling sites ranged from 1.48 to 1.64, indicating a low level of overall sediment contamination. Correspondingly, the Potential Ecological Risk Index (PERI) values ranged from 5.23 to 6.73, reflecting low ecological risk levels across all monitoring stations. These findings suggest that while the current sediment quality in this section of the Dong Nai River is stable, ongoing monitoring is essential to prevent potential risks associated with heavy metal accumulation, particularly for chromium and arsenic. The study underscores the importance of proactive environmental management to safeguard the aquatic ecosystem against future contamination threats.